Formulasi dan Uji Antibakteri Sediaan Pasta Gigi Ekstrak Parijoto (Medinilla speciosa) dengan Bovine Hidroksiapatit (BHA) - Teguh Imanto; Ronindya Gerry Aprastya (Universitas Pahlawan Tuanku Tambusai, 2026)
Dental caries is an oral health problem caused by bacteria such as Streptococcus mutans and Staphylococcus aureus. Parijoto fruit (Medinilla speciosa) contains secondary metabolites that have potential as antibacterial agent, while bovine hydroxyapatite (BHA) serves as a dental remineralizing agent. This study aims to formulate parijoto fruit extract toothpaste with BHA and evaluate its physical quality and antibacterial activity. This laboratory experimental study used four formulas, namely F0 (without extract), F1 (12.5% extract), F2 (15% extract), and F3 (17.5% parijoto extract). The extract was obtained by maceration method using 70% ethanol. Physical quality evaluation included organoleptic, homogeneity, pH, viscosity, and foam height, while antibacterial activity was tested by agar well diffusion method against Staphylococcus aureus and Streptococcus mutans. The Data were analyzed using statistical tests with significance level p < 0.05. Phytochemical screening results showed the presence of phenolics, flavonoids, saponins, and tannins. All formulas meet the physical quality requirements of toothpaste based on SNI 12-3524-1995. The pH values F0–F3 are 9,30 ± 0,05; 5,61 ± 0,03; 5,53 ± 0,03; and 5.75 ° 0.05. The variation of extract concentration significantly affected the viscosity and foam height (p < 0.05). Antibacterial test results showed that F3 has the highest inhibitory power against Staphylococcus aureus and significantly different from the positive control (p < 0.05). Based on the results of research, parijoto fruit extract with BHA has the potential as a toothpaste preparation with good physical quality and antibacterial activity.